2000
DOI: 10.1142/s0218127400001183
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation Analysis of Chen's Equation

Abstract: Anticontrol of chaos by making a nonchaotic system chaotic has led to the discovery of some new chaotic systems, particularly the continuous-time three-dimensional autonomous Chen's equation with only two quadratic terms. This paper further investigates some basic dynamical properties and various bifurcations of Chen's equation, thereby revealing its different features from some other chaotic models such as its origin, the Lorenz system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
140
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 384 publications
(143 citation statements)
references
References 4 publications
0
140
0
3
Order By: Relevance
“…1(d) for b ¼ 2.9). 38 First, we study the system (9) with a fixed b ¼ 1.5 and a varying noise intensity e. Recall that an analysis of the stochastic cycles of the Chen system was already reported earlier in Ref. 39.…”
Section: Analysis Of Noise-induced Chaos In the Chen Systemmentioning
confidence: 99%
“…1(d) for b ¼ 2.9). 38 First, we study the system (9) with a fixed b ¼ 1.5 and a varying noise intensity e. Recall that an analysis of the stochastic cycles of the Chen system was already reported earlier in Ref. 39.…”
Section: Analysis Of Noise-induced Chaos In the Chen Systemmentioning
confidence: 99%
“…This nonlinear model is based on the chaotic Chen's system [14], and it follows from its bifurcation analysis [15] that this interval system remains to be chaotic when c is fixed to be 28. It has been widely experienced that this chaotic system is relatively difficult to control as compared to the Lorenz system and Chua's system, which are all topologically non-equivalent, due to the prominent three-dimensional and complex topological features of its attractor, especially its rapid change in velocity in the x 3 -direction.…”
Section: Synthesis Of the Simplex Control Law Via Chaos Optimizationmentioning
confidence: 99%
“…Let the parameters of system (12) be a ¼ 45, b ¼ 1:5 and c ¼ 28, so that system (12) generates a periodic solution [15]. Starting from the initial state x r ð0Þ ¼ ½À1:7570; À1:9648; 7:9743 T , the three-dimensional phase portrait and the time-domain response of the reference x r ðtÞ are shown in Figs.…”
Section: Simulation Studymentioning
confidence: 99%
“…Since a description of the general case is rather messy and uneasy, at least notationally, to facilitate the description and discussion, we use a specific chaotic system as an example. This system is still not too special, in the sense that it unifies both the Lorenz [2] and the Chen systems [9,10], where the latter is the dual system of the former in a sense defined in [11]: The Lorenz system satisfies the condition a 12 a 21 > 0 while the Chen system satisfies a 12 a 21 < 0, where A ¼ ½a ij 3Â3 are the matrix of the linear part of the chaotic systems. Recently, L€ u u et al [12][13][14] found a unified chaotic system that not only includes the case of a 12 a 21 ¼ 0 [12] but also the Lorenz and Chen systems as two extreme cases.…”
Section: The Problem Formulationmentioning
confidence: 99%